A Case of Adrenergic Urticaria Associated with Vitiligo - Caroline Lang; Gürkan Kaya (MDPI AG, 2016)
Adrenergic urticaria is a rare form of urticaria, induced by a stress-induced concomitant release of epinephrine and norepinephrine. Here we describe the case of a 60-year-old female patient presenting with disseminated erythematous papules surrounded by a white halo and vitiligo lesions on the hands, arms, and feet. Histological examination of one of the erythematous papules showed a dermal inflammatory infiltrate composed of lymphocytes and eosinophils of perivascular and interstitial localization. After 2 weeks of treatment with antihistamines, the lesions disappeared completely.